Reducing or Widening the Gap? How the Educational Aspirations and Expectations of Turkish and Majority Families Develop During Lower Secondary Education in Germany - Sebastian Neumeyer; Melanie Olczyk; Miriam Schmaus; Gisela Will (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2022)
Differences in educational goals between immigrants and the majority population have often been analysed at specific stages in their educational career. Little is known about longitudinal trajectories and the development of group differences over time. By applying common explanations (immigrant optimism, relative status maintenance, blocked opportunities, ethnic networks and information deficits), we derived specific hypotheses about the development of educational aspirations and expectations over time, focusing on families from Turkey. We drew upon data from the National Educational Panel Study to assess how aspirations and expectations for the highest school degree develop over the course of lower secondary education in Germany's stratified school system. Applying a~multi-actor perspective, we observed trajectories reported by students and their parents. First, we analysed the development of group differences. In line with prior research, we found higher aspirations and expectations for Turkish students and their parents at the beginning of lower secondary education in Germany once social background and achievement differences were controlled for. Origin gaps for students' expectations and parents' aspirations decreased over the course of lower secondary education. Second, intraindividual trajectories of aspirations and expectations revealed that parents of Turkish origin were more likely to experience downwards adaptations than majority parents, whereas students of Turkish origin were more likely to hold stable high aspirations and expectations than majority students.
Keywords: 300; Educational ambitions; Ethnic inequality; Turkish origin; Immigrants; Trajectories; Bildungsziele; Ethnische Ungleichheit; Türkische Herkunft; Migranten; Verläufe